Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.neurobiolaging.2010.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in cell cycle-related proteins in lymphoblasts from carriers of the c.709-1G>A PGRN mutation associated with FTLD-TDP dementia

Abstract: Frontotemporal lobar degeneration with neuronal inclusions containing TAR DNA binding protein 43 (TDP-43) is associated in most cases with null-mutations in the progranulin gene (PGRN). While the mechanisms by which PGRN haploinsufficiency leads to neurodegeneration remained speculative, increasing evidence support the hypothesis that cell cycle reentry of postmitotic neurons precedes many instances of neuronal death. Based in the mitogenic and neurotrophic activities of PGRN, we hypothesized that PGRN deficit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 61 publications
4
38
0
Order By: Relevance
“…25,45 Because most of the asymptomatic carriers are younger than the patients with FTD, it is suggested that these features are probably early etiologically relevant events during the development of this disorder. These presymptomatic GRN mutation carriers showed no symptoms of disease, but previous studies have described poorer neuropsychological performance and distinctive agerelated cortical thinning in asymptomatic individuals compared with controls 74,75 that may reflect a presymptomatic phase of the disease.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…25,45 Because most of the asymptomatic carriers are younger than the patients with FTD, it is suggested that these features are probably early etiologically relevant events during the development of this disorder. These presymptomatic GRN mutation carriers showed no symptoms of disease, but previous studies have described poorer neuropsychological performance and distinctive agerelated cortical thinning in asymptomatic individuals compared with controls 74,75 that may reflect a presymptomatic phase of the disease.…”
Section: Resultsmentioning
confidence: 99%
“…Parametric tests were therefore used in the statistical analysis. Based on the expertise achieved in previous works 25,44,45 we expected that with the sample size that we used and the significance level that we established the variability within groups would be low enough and the power to detect differences between groups would be high enough to J Psychiatry Neurosci 2016;41(4) ensure a statistical power above 0.9. Statistical significance was estimated using the Student t test or, when appropriate, using 1-way and 2-way analyses of variance (ANOVA) followed by the Bonferroni test for multiple comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations